1990
DOI: 10.1007/bf01313252
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the euphausiidsThysanoessa raschi, T. inermis andMeganyctiphanes norvegica in �safjord-deep, northwest-Iceland

Abstract: Abstract. The seasonal abundance, distribution, maturity, growth and population dynamics of the euphausiids Thysanoessa raschi (M. Sars, 1864), T. inermis (Kroyer, 1846) and Meganyctiphanes norvegica (M. Sars, 1857) were studied in Isafjord-deep, a fjord in northwest Iceland, from February 1987 to February 1988 Sampling was made at nine stations along the length of the f~ord at approximately monthly intervals, along with hydrographic measurements and water sampling for nutrient analysis and measurements of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
(27 reference statements)
5
27
0
Order By: Relevance
“…Several authors have suggested that spawning of Thysanoessa spp. coincides with the onset of the phytoplankton spring bloom (Einarsson 1945, Berkes 1976, Lindley & Williams 1980, Falk-Petersen & Hopkins 1981, Astthorsson 1990, Gislason & Astthorsson 1995, Dalpadado 2006, Plourde et al 2010, which is further supported by the present results. During the study period, there was a second peak in egg abundance at the beginning of July, indicating a second spawning event, as described by MacDonald (1928) for T. raschii in the Firth of Clyde.…”
Section: Spawning Maturity and Seasonal Distribution Of Larvaesupporting
confidence: 80%
See 3 more Smart Citations
“…Several authors have suggested that spawning of Thysanoessa spp. coincides with the onset of the phytoplankton spring bloom (Einarsson 1945, Berkes 1976, Lindley & Williams 1980, Falk-Petersen & Hopkins 1981, Astthorsson 1990, Gislason & Astthorsson 1995, Dalpadado 2006, Plourde et al 2010, which is further supported by the present results. During the study period, there was a second peak in egg abundance at the beginning of July, indicating a second spawning event, as described by MacDonald (1928) for T. raschii in the Firth of Clyde.…”
Section: Spawning Maturity and Seasonal Distribution Of Larvaesupporting
confidence: 80%
“…However, the absence of smaller individuals and non-fertilized females of M. nor vegica suggests that this species does not reproduce in the fjord but is advected from outside the fjord (Agersted & Nielsen 2014). Astthorsson (1990) respectively. The spawning in Kapisigdlit is therefore assumed to be that of Thysanoessa spp.…”
Section: Spawning Maturity and Seasonal Distribution Of Larvaementioning
confidence: 98%
See 2 more Smart Citations
“…It is noted that the spawning season of this euphausiid overlaps the period of the spring phytoplankton bloom both in the central Japan Sea (Chiba & Saino 2002) and in the Oyashio region (Kasai et al 2001). Coincidence of reproduction and the spring phytoplankton bloom has also been reported for other subarctic Thysanoessa euphausiids (T. inermis Krøyer and T. raschii M. Sars) in the Atlantic Ocean (Falk-Petersen & Hopkins 1981, Astthorsson 1990.…”
Section: Life Cycles Of Thysanoessa Inspinata and T Longipesmentioning
confidence: 88%